Designing selective inhibitors for calcium-dependent protein kinases in apicomplexans. (July 2015) - Hui, Raymond; El Bakkouri, Majida; Sibley, L. David
Highlights Apicomplexan parasites contain a family of plant-like calcium-dependent serine-threonine protein kinases (CDPKs) that control a variety of essential functions. CDPKs contain an unusual domain architecture and use a unique activation mechanism that is based on an autoinhibitory calmodulin-like domain fused to the C terminus of the kinase domain. Several CDPKs have been validated as potential drug targets based on genetic experiments demonstrating that they are essential for parasite growth or survival. Unique chemical scaffolds have been exploited to develop selective inhibitors of essential CDPKs in parasites, offering promise as new therapeutic leads.